Technology Penetration & Adoption in An Unstructured Retail Market of Kolkata, India - Subir Chattopadhyay, Joydeep Mookerjee (Mathematical Statistician and Engineering Applications, 2022)
On 8 November 2016, the Indian government announced demonetization to eradicate black money hoarding, counterfeit notes, and terror financing. Although this initiative did help the country thrive, it did so at the expense of the general population, businesses, the financial markets, and the financial system. Since then, there has been an increase in businesses that do not accept cash and prefer classless online transactions. Small enterprises servicing the public were the worst hit. Though demonetization has changed commercial transactions, most small retailers haven’t shifted to e-payment. After a few years of demonetization, the Covid-19 pandemic happened, and the no-contact and social distance protocol motivated many small businesses to adopt a new era of retail technology. The forced transformation was observed evidently in metro cities in India but not that much in suburban and rural India. The paper discusses 110 small retailers’ owners in Khidirpur Market, one of the biggest markets in Kolkata, West Bengal, India. The survey was conducted to establish if they use cash or e-payments and identify their marginal gains and services taxes if they paid any. The paper also points out how they finance their business. The demographics are spread interestingly and cover four broadly categorized small retailers: small groceries (Kirana), footwear, and pharmacy stores (ayurvedic, homeopathy, and allopathy medicines). The survey revealed that small retailers like Pharmacy stores have begun adopting mobile payment solutions, printed billing systems, and automatic inventory management. But this technology adoption is not a remarkable transformation.